PENGARUH ORGANIZATIONAL LIFE CYCLE TERHADAP ORGANIZATIONAL PERFORMANCE PADA PERUSAHAAN TERBUKA (TBK) DI SURABAYA - Grandy Septian Ongko; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the direct influence of organizational life cycle to organizational performance in the Public Companies in Surabaya. This study take sample of 30 public companies located in Surabaya. The study used a quantitative research and the data were obtained by distributing questionnaires to the companies and through the company's financial statements. This study used path analysis modeling techniques with PLS software tools. The results showed that there was negative influence of organizational life cycle to organizational performance in overall, positive influence of organizational life cycle to employee oriented measuress in organizational performance in partially, positive influence of organizational life cycle to customer oriented measuress in organizational performance in partially, negative influence of organizational life cycle to return on investment in organizational performance in partially